1999
DOI: 10.1190/1.1444588
|View full text |Cite
|
Sign up to set email alerts
|

Variogram analysis of helicopter magnetic data to identify paleochannels of the Omaruru River, Namibia

Abstract: The geomagnetic field over sedimentary basins is very sensitive to variations in basement depth. Therefore, magnetic surveys are widely used to map basement topography in petroleum and groundwater exploration. We propose variogram analysis as a more accurate alternative to power spectral methods. Data variograms are computed from aeromagnetic flight-line data. To estimate depth, the data variograms are compared with model variograms for a range of source depths. We use the exact space domain counterparts of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…These findings were further confirmed by the authors in another publication (Pilkington and Todoeschuck 1995). Maus et al (1999) conducted variogram analysis on magnetic data in Canada and found the data to exhibit scaling behavior as function of the horizontal distance. Studies in the soil science field have shown that the soil pore structure is fractal (Perrier et al 1996;Baveye et al 1998).…”
Section: Multifractal Modeling and Magnetic Datasupporting
confidence: 67%
“…These findings were further confirmed by the authors in another publication (Pilkington and Todoeschuck 1995). Maus et al (1999) conducted variogram analysis on magnetic data in Canada and found the data to exhibit scaling behavior as function of the horizontal distance. Studies in the soil science field have shown that the soil pore structure is fractal (Perrier et al 1996;Baveye et al 1998).…”
Section: Multifractal Modeling and Magnetic Datasupporting
confidence: 67%
“…These findings were further confirmed by the authors in another publication (Pilkington and Todoeschuck 1995). Recently, Maus et al (1999) conducted variogram analysis on magnetic data in Canada and found the data to exhibit scaling behavior as function of the horizontal distance.…”
Section: Introductionsupporting
confidence: 69%
“…Prior studies Todoeschuck 1993, 1995;Pilkington et al 1994;Maus et al 1999) found that the spatial distribution of magnetic data exhibit monofractal scaling. Our approach is more general because it allows for multifractality, while treating monofractality as a particular case.…”
Section: Discussionmentioning
confidence: 99%
“…He described that the power spectrum of gravity anomaly is given by the product of functions that describe source parameters depth, thickness horizontal dimensions and density contrast of the causative body. Maus (1999) and Maus et al (1999) showed that model variograms describe the space domain statistics of gravity and magnetic data. They proposed variogram analysis of gravity and magnetic data as an alternative to power spectrum method.…”
Section: Methodsmentioning
confidence: 99%